Previous year Question of jee mains
Chapter:- application and derivatives
Attachments:
![](https://hi-static.z-dn.net/files/d38/5cb3abc4cc66c8144f6be30d526d5784.jpg)
Answers
Answered by
2
The correct option is (1)
Attachments:
![](https://hi-static.z-dn.net/files/dde/865de04f7bad8e545493214d18d459c2.jpg)
Answered by
9
EXPLANATION.
⇒ f(x) = 4x³ - 3x²/6 - 2sin x + (2x - 1)cos x.
As we know that,
Differentiate the equation, we get.
⇒ f'(x) = (2x² - x) - 2cos x + 2cos x - sin(2x - 1).
⇒ f'(x) = (2x² - x) - sin x (2x - 1).
⇒ f'(x) = x(2x - 1) - sin x (2x - 1).
⇒ f'(x) = (x - sin x)(2x - 1).
As we know that,
⇒ x - sin x > 0 for x > 0.
⇒ x - sin x < 0 for x < 0.
⇒ f'(x) ≥ 0 = x ∈ (-∞, 0] ∪ [1/2, ∞).
⇒ f'(x) ≤ 0 = x ∈ [0, 1/2].
⇒ f(x) is increasing = [1/2, ∞).
Option [1] is correct answer.
Attachments:
![](https://hi-static.z-dn.net/files/d5b/f7e58fd070943b13f43beeebff1dd5ab.jpeg)
Similar questions